Quantum Cascade Lasers in Biomedical Infrared Imaging. Issue 10 (October 2015) - Bird, Benjamin; Baker, Matthew J.
<x xml:space="preserve">Abstract</x> Technological advances, namely the integration of quantum cascade lasers (QCLs) within an infrared (IR) microscope, are enabling the development of valuable label-free biomedical-imaging tools capable of targeting and detecting salient chemical species within practical clinical timeframes.